Study of the copper structure samples externed to extreme influences - Bektasova, G.S.; Issina, K.M.; Imanzhanova, G.T.; Kveglis, L.I.; Kantai, N.; Nedobitkov, A.I.; Sadibekov, A.B. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
This work is devoted to the study of changes in the crystal structure, chemical and phase composition of copper samples subjected to extreme effects of temperature, pressure and electromagnetic fields. With the help of X-ray diffraction, as well as microanalysis, it was revealed that the plastic deformation of copper wires in the car power supply system leads to the formation of a superconducting Cu2O phase. This is the reason for the rapid ignition of the car, as it leads to a sharp increase in the magnitude of the electric current and temperature in the plastic deformation zone of copper wires. During explosion welding of copper samples, the Cu2O phase appears on their surface, which has superconducting properties. This significantly changes the electrophysical properties of copper samples. In metallurgical processes during the smelting of copper products, there is a possibility of the appearance of a superconducting Cu2O phase. When modifying a copper melt with hardening additives, the superconducting Cu2O phase makes it possible to obtain fracture-resistant copper products with high electrical conductivity. Plastic deformation of a copper foil 30 mkm thick by a magnetic field generated by a current of 180 kA leads to the formation of a texture and rupture of the foil. This has been detected using X-ray diffraction, as well as optical and scanning electron microscopy.
Экстремалды әсерлерге ұшыраған мыс үлгілерінің құрылымын зерттеу
Исследование структуры медных образцов, подвергнутых экстремальным воздействиям
Keywords: copper samples; ignition zone; plastic deformation; explosion processing; deformation by electromagnetic wave flow